Предмет: Химия,
автор: Unico0
Осуществить превращение Sb-->Sb2O3-->Sb2(SO4)3-->Sb(OH)2-->SbCl3
Ответы
Автор ответа:
0
4Sb + 3O2 = 2Sb2O3
Sb2O3 + 3H2SO4 = Sb2(SO4)3 + 3H2O
Sb2(SO4)3 + 6NaOH = 3Na2SO4 + 2Sb(OH)3
Sb(OH)3 + 3HCl = SbCl3 + 3H2O
Sb2O3 + 3H2SO4 = Sb2(SO4)3 + 3H2O
Sb2(SO4)3 + 6NaOH = 3Na2SO4 + 2Sb(OH)3
Sb(OH)3 + 3HCl = SbCl3 + 3H2O
Похожие вопросы
Предмет: Химия,
автор: gulzhanzhaksybergen
Предмет: Английский язык,
автор: Аноним
Предмет: Қазақ тiлi,
автор: bajgalievaaruzan07
Предмет: Математика,
автор: lukianova2009